Persepsi Pengguna terhadap Kualitas Komunikasi Chatbot AI Shopee: Studi Kualitatif pada Konsumen Aktif Marketplace Shopee - Muhammad Farid Affan; Fitria Nur ‘Aini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to explore how users' perceptions of the chatbot on the Shopee platform influence user satisfaction and loyalty. The research employs a qualitative approach with in-depth interviews to gather users' experiences and views on their interactions with the chatbot. The findings reveal that three key factors—clarity of responses, ease of access, and relevance of information—are crucial in determining user satisfaction. Users who found the chatbot's responses clear and easily understood, along with quick access, were generally more satisfied with the service provided. However, despite achieving user satisfaction, loyalty to the platform has not been fully established. This is due to the chatbot's limitations in building emotional connections with users and its inability to handle more complex issues. While the chatbot is effective in providing automated solutions for simple problems, it lacks the empathy and personalized attention necessary when users encounter more intricate issues or require a deeper level of interaction. These findings highlight that although chatbots can enhance the efficiency of basic customer service, they cannot fully replace human interaction, particularly in customer service contexts that require emotional engagement and a deeper understanding of the user's needs. To foster stronger user loyalty, a combined approach involving both technology and human interaction is essential. The chatbot can address routine issues, while more complex matters should be referred to customer service representatives who can offer empathetic and tailored solutions. The recommendation from this study is for Shopee platform developers and sellers to strategically optimize chatbot use while maintaining human interaction that is adaptable, in order to enhance user satisfaction and loyalty.